The use of game pedagogical technologies in pedagogical theory and practice (Pedagogy of Higher and Secondary Education, 2021)
In the article it is considered the conception 'playing pedagogical activity', 'didactic game', 'playing pedagogical technology', the structure and the aim of a didactic game; it is analysed functions of the playing activity; the function of socialization, of international communication, of self-realization, communicative, diagnostic, playing-therapeutic corrective, entertaining, humane; it is exposed the aims of didactic games: educational, developing, social.
Keywords: playing pedagogical activity; didactic game; playing pedagogical technology